Coculture with Low‐Dose SWCNT Attenuates Bacterial Invasion and Inflammation in Human Enterocyte‐like Caco‐2 Cells. Issue 34 (11th June 2015) - Chen, Hanqing; Wang, Bing; Zhao, Ruifang; Gao, Di; Guan, Ming; Zheng, Lingna; Zhou, Xiaoyan; Chai, Zhifang; Zhao, Yuliang; Feng, Weiyue
<x xml:space="preserve">Abstract</x> Single walled carbon nanotubes (SWCNTs) have been shown to be highly effective against a wide range of bacteria. Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) infection is a well‐known mediator to prolong hospitalization and initiate chronic inflammation, yet the biological effects of SWCNTs on the pathogen‐infected enterocytes remain unclear. Herein, it is shown that the low‐dose SWCNT treatment attenuates the human enterocyte‐like Caco‐2 cells from the damage of E. coli and S. aureus infection by suppressing NLRP3 inflammasome activation. The relatively low‐dose (1 and 10 μg mL−1) SWCNT treatments reduce the adhesion and invasion of E. coli and S. aureus to Caco‐2 cells, increase the cell viability and proliferation, reduce the tight junction permeability, and restitute the integrity of cell surface microvilli structure, meanwhile has low cytotoxicity to the host cells. The low‐dose SWCNT treatment further reduces the NLRP3‐mediated IL‐1β secretion in the infected cells. The results identify that a low‐dose SWCNT treatment serves a protective function for the E. coli‐ and S. aureus‐infected Caco‐2 cells by negatively regulating mitochondrial reactive oxygen species‐mediated NLRP3 inflammasome activation.